(untitled) (Research, Society and Development, 2021)
The aim of the study was to investigate the eating behavior of preschool children during the social isolation period of the first wave of COVID-19 in Fortaleza, Ceará. This is a cross-sectional observational study, carried out with caregivers of preschool children aged from 2 to 6 years. The PENSE questionnaire (IBGE) was used to collect socio-economic data and the data referring to eating behavior was used the CEBQ. 286 parents (mother and father) and their children participated in the research, of which 53.8% were female. The preschoolers in the study constituted 5.2% of infant I, 9.8% infant II, 14.7% infant III, 20.6% infant IV, 23.1% infant V, 15.4% 1-year elementary school and 11.2% did not attend school. As for the education of most mothers, 83.9% completed higher education. Regarding the number of people who lived in the household, 44.4% lived with 4 people and 73.1% had 1 child. The highest mean values ​​are present in the dimension "Pleasure to eat" (EF) and "Response to satiety" (SR), while the lowest refer to the dimensions "About Emotional Intake" (EOE) and "Response to food" (FR). The statistical results of the “Food Fussiness” (FF) subscale point out important aspects about the selectivity in the sample of the present study, demonstrating a good tendency to picky eating. The dimension with the lowest mean was “Emotional Overeating”, demonstrating that when confined due to the COVID-19 pandemic, preschoolers still have EOE lower than all other subscales. It follows that children in preschool stage have presented a higher prevalence in subscales that are linked to food avoidance behavior.